Salib Yesus – Penderitaan Maria Devosi Maria dalam Ibadat Jalan Salib Versi Solor-Lamaholot - Paul Budi Kleden (Jurnal Ledalero, 2011)
Devotion to Mary is one of the most popular religious practices among Catholics, and can be considered one of the oldest forms of popular religiosity. Marian devotions emerged spontaneously as a mixture of elements from local cultures and the Christian faith. However, such practices can become problematic when they overstress certain aspects of human experience together with the role of Mary. This article discusses a text of "The Way of the Cross" which was composed in a dialect of the Lamaholot language as used on the isle of Solor, East Flores. Kata-kata kunci: devosi, jalan salib, penderitaan, ratapan, harapan